ANALISIS NARATIF FUNGSI TOKOH EDI DARMAWAN SALIHIN DAN OTTO HASIBUAN PADA FILM DOKUMENTER ICE COLD: MURDER, COFFEE, AND JESSICA WONGSO - Pratama, Salman Wahyu; ., Tsuroyya (Universitas Negeri Surabaya, 2024)
This research aims to examine the story structure and function of the characters Edi Darmawan and Otto Hasibuan in the documentary Ice cold. To answer the formulation of the problem, the researcher used Nick lacey's theory of structure and Algirdas Greimas' theory of action. The results of the study revealed that this film was composed with direct stages of disturbances to balance, awareness of disturbances, and ended with efforts to correct disturbances. The results of the study also found that the two characters had important roles in the film. They are inconsistent in occupying one of the roles. There are times when they occupy a position as a subject but there are times when they also occupy a position as a barrier. Edi Darmawan in every story always inserts logic that Jessica is guilty. Meanwhile, Otto Hasibuan focused on proving irregularities in the process of determining the defendant and the trial.